Interpretation of Platelets in The Horse - Satué, K.; Gardón, J. C.; Muñoz, A. (Journal of Hematology Research, 2017)
Currently we can consider that, in addition to its role in hemostasis, platelets also participate in other important processes such as thrombosis, inflammation, tissue remodeling and the innate defense mechanisms. The hemostatic activity of platelets includes different events to stop bleeding. Within these functions we can mention the adhesion to the endothelium of the affected blood vessel, the activation, the aggregation, and the release of substances that initiate hemostatic events, and also the providing a phospholipid surface for activation of numerous coagulation factors. Similarly, platelets release multiple growth factors responsible for regulating the growth and division of endothelial cells and fibroblasts. In this way, among other things, angiogenesis and tissue regeneration are favored. Platelets also participate in inflammatory processes by the release of factors that initiate the inflammatory cascade and favor the chemotaxis of neutrophils, monocytes, macrophages, acute phase proteins and target cell signaling. Finally, platelets participate in the immune response by interacting with the complement system and immunoglobulins.